2017
DOI: 10.1159/000452828
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Bullous Pemphigoid Patient with Rituximab Who Was Refractory to Corticosteroid and Omalizumab Treatments

Abstract: Omalizumab is a humanized monoclonal antibody which is an FDA-approved treatment of severe allergic asthma and inhibits IgE binding to FcεRI. According to increasing evidence of IgE inhibition, omalizumab was suggested as a therapeutic approach for bullous pemphigoid (BP). Rituximab has been reported to be effective in various autoimmune diseases, including autoimmune bullous dermatoses. A specific protocol for the use of rituximab to treat BP patients is not yet available. There are only small case series and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The rituximab group had 36 publications ( 13 48 ), including 5 prospective studies, 9 retrospective studies, and 22 case series or reports. The omalizumab group had 28 publications ( 17 , 49 75 ), including 1 prospective study, 1 retrospective study, and 26 case series or reports. While the dupilumab group had 11 publications ( 59 , 73 , 76 84 ), including 2 retrospective studies and 9 case series or reports.…”
Section: Resultsmentioning
confidence: 99%
“…The rituximab group had 36 publications ( 13 48 ), including 5 prospective studies, 9 retrospective studies, and 22 case series or reports. The omalizumab group had 28 publications ( 17 , 49 75 ), including 1 prospective study, 1 retrospective study, and 26 case series or reports. While the dupilumab group had 11 publications ( 59 , 73 , 76 84 ), including 2 retrospective studies and 9 case series or reports.…”
Section: Resultsmentioning
confidence: 99%
“…In BP patients, several studies demonstrated a relationship between the titre of BP180 NC16A IgG and the disease severity and a fluctuation of these titres between days 0, 60 and 150 may predict outcome . In this line, treatment with adjuvant immunoadsorption or rituximab combined or not with intravenous immunoglobulins that reduce BP180 autoantibody concentration has been associated with clinical improvement and allows progressive withdrawal of corticosteroid or other immunosuppressants . Circulating antibasement membrane autoantibodies are mainly of the IgG isotype, with the IgG4 and IgG1 as the predominant IgG subclasses represented .…”
Section: Bp‐related Autoantibodies As Biomarkers Of Bp Diseasementioning
confidence: 99%
“…40 Interestingly, there are reports of patients with rituximab-refractory bullous pemphigoid responding to omalizumab and vice versa, indicating the intricacies of the types of autoantibodies, their specific pathogenic actions and wide inherent inter-individual variations in this disease. [41][42][43] Omalizumab has also been used successfully in the treatment of infantile bullous pemphigoid. 44 Inhibiting Cytokines, Chemokines and Complements…”
Section: Omalizumabmentioning
confidence: 99%